DOP68 CD-TREAT diet induces remission and improves quality of life in an open label trial in children and adults with active Crohn's Disease. (21st January 2022) - Svolos, V; Hansen, R; Russell, R; Gaya, D R; John Paul, S; Macdonald, J; Nichols, B; Papadopoulou, R; Logan, M; Mckirdy, S; Gervais, R; Ijaz, U; et al.
Abstract: Background: Exclusive enteral nutrition (EEN) is an established induction treatment for active Crohn's disease (CD) with a proposed mechanism of action involving the gut microbiome. We have previously shown that CD-TREAT diet, a food-based diet with similar dietary profile to EEN, improves rat ileitis and replicates the effect of EEN on the gut microbiome of healthy volunteers and animal models. Here, we test the efficacy of CD-TREAT diet to induce clinical remission in active CD. Methods: This is an open-label study in children (wPCDAI≥12.5) and adults (HBI≥5) with active CD. Primary outcome was clinical response (wPCDAI fall≥17.5; HBI fall≥3) or clinical remission (wPCDAI< 12.5; HBI<5) after 8 week treatment with CD-TREAT. Secondary outcomes included improvement of quality of life (QoL) and reduction in faecal calprotectin (FC) levels. Since CD-TREAT diet is gluten-free, adherence to treatment was assessed by the detection of the gluten immunogenic peptide (GIP) in faeces. Data are presented with median (IQR). Results: 25 children, [age, 14.4 (12.5, 15.7) years] and 32 adults, [age, 32.6 (24.2, 43.9) years] were treated. 7 (12%) failed treatment and n=10 (18%) dropped out during the first 2 weeks of treatment due to palatability issues. In patients who completed 8 weeks of CD-TREAT course (n=40), 85% and 78% achieved clinical response and remission, respectively. CD-TREAT diet improved QoL in children [IMPACT-III score, baseline: 136 (122, 143) vs 8weeks: 148 (133, 153), p<0.01] and in adults [sIBDq score, baseline: 30 (26, 45) vs 8weeks: 60 (48, 64), p<0.001]. Faecal GIP decreased during treatment [ng/g stool, baseline: 1250 (589, 1250), 4weeks: 0 (0, 269), 8weeks: 0 (0, 329), mg/mg, p<0.001 for both] showing adherence with the CD-TREAT diet. However, 33% and 40% of the patients had detectable faecal GIP at 4 and 8 weeks, respectively, revealing at least partial non-adherence. 30% of patients who completed CD-TREAT (n=12/40) experienced >50% FC reduction. Median FC levels decreased significantly? in the group of patients (n=22) who had undetectable GIP at 4 or 8 weeks [mg/kg FC, baseline: 1190 (361, 1129); 8weeks: 534 (92, 1230), p<0.01]. Conclusion: CD-TREAT diet improved disease activity indices and QoL in the majority of patients who completed treatment and decreased FC in those who were most likely to be compliant. Future RCT should aim to compare CD-TREAT with other induction treatments and improve meal variety and palatability to improve compliance and reduce drop-out rates.